Analyzing Challenges and Opportunities in Entrepreneurship Development: A Study of University Students in Rawalpindi and Islamabad. - Ullah, Naqeeb; Asghar, Umair (2024)
This study examines the influence of financial, technical, and cultural barriers on entrepreneurial growth in Pakistan, focusing specifically on college students in Rawalpindi and Islamabad. The research addresses a critical issue: while Pakistan’s economic environment and various government initiatives offer substantial opportunities for business development, excessive government intervention is identified as a major impediment to entrepreneurial innovation and risk-taking. To investigate this, primary data was collected using a structured questionnaire administered to college students. The study employs correlation analysis to explore the relationship between these barriers and the capacity for business growth, as well as to assess the interactions among the different types of impediments. Financial barriers include limited access to funding and financial resources; technical barriers encompass a lack of technical skills and infrastructure; and cultural barriers involve societal attitudes and norms that may hinder entrepreneurial activities.The findings reveal that while government initiatives are well-intentioned, their excessive interference can undermine the entrepreneurial spirit by creating regulatory and bureaucratic hurdles. This research provides critical insights into how these barriers impact the entrepreneurial ecosystem and highlights the need for a balanced approach to government intervention. By offering a detailed analysis of these factors, the study aims to assist scholars and policymakers in developing more effective strategies to enhance Pakistan’s entrepreneurial environment, thereby fostering sustainable business growth and innovation.